EFFECT OF PLATELET RICH FIBRIN AND INJECTABLE PLATELET RICH FIBRIN ON BONE HEALING (COMPARATIVE STUDY ON SHEEP) - NAYYEF, MOHAMED SAMYAN; NAJI, JIYAR M. (Journal of Duhok University, 2023)
Objective Aim of study: This study aims to compare the effect of the PRF , i-PRF on bone defect healing. defectThe Platelet-rich fibrin (PRF) was first developed in France by Choukroun in 2001, an autologous biomaterial was developed that consists of leucocytes and platelet-rich fibrin. (PRF) (Choukroun et al 2001A more recent iteration of platelet-rich fibrin, known as injectable platelet-rich fibrin, has been developed to be utilized in a flowable form. This variant can be prepared at varying speeds and durations. Both platelet-rich fibrin forms have the potential to aid in the regeneration of both soft and hard tissues in areas affected by damage. The presence of bone abnormalities can result in both aesthetic and functional impairments, hence rendering dental rehabilitation more challenging. The aim of this study is to histologically evaluate the process of hard tissue healing in bone defects that have been treated with platelet-rich fibrin (PRF) and its injectable version, known as i-PRF. Results :The presence of inflammation was noted during the initial weeks following surgery, accompanied by a limited proliferation of osteoblasts in platelet-rich fibrin (PRF) compared to injectable platelet-rich fibrin (i-PRF). In the 16th week, the presence of osteoblasts and fibrosis was seen, indicating the development of new and mature bone